2022
DOI: 10.1002/cam4.5519
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire‐ and linkage‐based outcomes in Dutch childhood cancer survivors: Methodology of the DCCSS LATER study part 1

Abstract: Background: Childhood cancer survivors are at risk for developing long-term adverse health outcomes. To identify the risk of and risk factors for specific health outcomes, well-established cohorts are needed with detailed information on childhood cancer diagnosis, treatment, and health outcomes. We describe the design, methodology, characteristics, and data availability of the Dutch Childhood Cancer Survivor Study LATER cohort (1963-2001 part 1; questionnaire and linkage studies. Methods: The LATER cohort inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 70 publications
(103 reference statements)
0
29
0
Order By: Relevance
“…Parents' age, sex, level of education and number of children were the included sociodemographic characteristics. The latter two were obtained from their survivor child in either DCCSS LATER two or DCCSS LATER 1 22 . Child medical characteristics were CNS diagnosis (vs. other diagnoses), recurrence, age at diagnosis and time since diagnosis, and were obtained from the DCCSS LATER registry 22 …”
Section: Methodsmentioning
confidence: 99%
“…Parents' age, sex, level of education and number of children were the included sociodemographic characteristics. The latter two were obtained from their survivor child in either DCCSS LATER two or DCCSS LATER 1 22 . Child medical characteristics were CNS diagnosis (vs. other diagnoses), recurrence, age at diagnosis and time since diagnosis, and were obtained from the DCCSS LATER registry 22 …”
Section: Methodsmentioning
confidence: 99%
“…Participating survivors and siblings were asked to complete a questionnaire on general health and lifestyle. Because survivors and siblings who participated in the LATER 1 questionnaire study in 2012-2014 7 already filled out extensive data on health and lifestyle, those persons were only asked to complete a short repeat version of this questionnaire focusing on main health outcomes only (Table S3). Survivors and siblings who did not participate in the LATER 1 questionnaire study were asked to complete the full questionnaire on general health and lifestyle (Table S3).…”
Section: Questionnairesmentioning
confidence: 99%
“…The methods for this study are described in a separate paper. 7 In this paper, we describe the methodology and provide the first To achieve these goals, the DCCSS LATER study group designed, a priori, 16 sub-studies based on health outcomes (Table S1). Eligible The specific methodologies of sub-studies will be described in separate papers.…”
Section: Introductionmentioning
confidence: 99%
“…Although small studies on specific childhood cancer types have reported on side effects of 3D-RT, 21 large-scale observational studies including follow-up of patients beyond the 5-year survival mark are rare to date. 22 This study has expanded upon the resources of the Dutch Childhood Cancer Survivor Study (DCCSS) LATER Cohort of 5-year CCS 10,11,23 with the purpose of filling this evidence gap. In particular, the overall aim of the Dutch Pediatric 3D-RT study is to evaluate adverse late health outcomes among children treated with radiotherapy in the era of CT-based treatment planning, and to assess dose response relationships for selected health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This study has expanded upon the resources of the Dutch Childhood Cancer Survivor Study (DCCSS) LATER Cohort of 5‐year CCS 10 , 11 , 23 with the purpose of filling this evidence gap. In particular, the overall aim of the Dutch Pediatric 3D‐RT study is to evaluate adverse late health outcomes among children treated with radiotherapy in the era of CT‐based treatment planning, and to assess dose response relationships for selected health outcomes.…”
Section: Introductionmentioning
confidence: 99%